The New Public Management Theory in the British Health Care System: A Critical Review. (September 2015) - Simonet, Daniel
This article analyzes health care reforms in the United Kingdom following the introduction of New Public Management (NPM) theory–inspired reforms. NPM has taken root deeply in the United Kingdom. This article looks at its impact on health care markets on the performance of health care organizations and on patients. It further seeks to address whether NPM prevents wastage and opportunism in health care. And finally, this article seeks to confirm whether rationality and accountability are greater under NPM or not. This article concludes that NPM reforms have failed to deliver on their own goals. There have been significant undesirable side effects and misfits between policy announcements and NPM implementation. Still, NPM adoption in health care has contributed to changing the Anglo-Saxon model of capitalism.